Healthcare utilization and medical expenditure of Korean psoriasis patients: A descriptive result using a health insurance database. Issue 24 (June 2018) - Ha, Dongmun; Lee, JeeYeon; Kim, Dajeong; Oh, In-Sun; Lee, Eui-Kyung; Shin, Ju-Young
Abstract: Background: Epidemiological evidence regarding healthcare utilization and medical expenditure of patients with psoriasis in Korea is needed. To analyze the differences in healthcare utilization and financial burdens between patients with and without psoriasis and compare these patterns according to the disease severity. Methods: We conducted a descriptive cross-sectional study using a sample of the National Health Insurance database between January 1, 2012 and December 31, 2013. We included patients diagnosed with psoriasis and those with nonpsoriasis skin diseases, matched for age, sex, income, and geographical region. The patients with psoriasis were further divided into mild and moderate-to-severe psoriasis groups. Each patient was followed up for 1 year to estimate their healthcare utilization and medical expenditure since their initial diagnosis. Healthcare utilization was defined as the sum of outpatient visits and inpatient stays per person. We conducted McNemar test or Bowker test of symmetry to compare the baseline characteristics and used the Wilcoxon matched-pair signed-rank test to compare the healthcare utilization and direct costs with a 5% significance level. Results: Our study subjects were 4016 patients with psoriasis and equally matched 4016 patients with nonpsoriasis skin diseases. Compared with patients without psoriasis, those with psoriasis had more days of healthcare service use (5.26 vs 4.19, P  < .001) and higher medical expenditures within 1 year per person (209, 320 vs 117, 968 won, P  < .001). Patients with moderate-to-severe psoriasis had more days of healthcare service use (12.71 vs 3.25, P  < .001) and higher medical expenditures within 1 year per person (611, 688 vs 107, 445 won, P  < .001) than those with mild psoriasis. Conclusion: Patients with psoriasis had higher burdens of healthcare utilization than those without psoriasis, and patients with moderate-to-severe psoriasis had the greatest burdens. Abstract : Supplemental Digital Content is available in the text